Exemption from the position of Head of the Health Office by the Regent of Deli Serdang (Study of the Decision of the State Administrative Court Number 38/G/2023/PTUN. MDN Siyasah Qadhaiyyah Perspective) - Risalah Adha Harahap; Tetty Marlina Tarigan (Warmadewa Press, 2024)
In this study, the state administrativ Court's (PTUN) Decision Number 38/G/2023/PTUN.MDN is analyzed which is related to the dismissal of the Head of the Deli Serdang Health Office by the Regent. The main issue raised is the legality of the dismissal from the perspective of administrative law and the principles of siy?sah qa?h?’iyyah. This research employs a library research method aimed at collecting and analyzing data from various literature sources, including books, journals, legislation, and relevant court decisions. The research methodology consists of several main approaches, namely normative juridical studies, legislative approach, conceptual approach, and case approach. The key findings indicate that although the Regent has the authority to impose disciplinary sanctions, the dismissal decision did not meet the proper procedural standards. The court found that the decision was procedurally flawed and unsupported by sufficient evidence. Additionally, the Regent was deemed unjust for not providing adequate explanation regarding the alleged violations committed by the Plaintiff and appeared to favor other officials involved in similar violations. The conclusion of this research emphasizes the importance of justice, transparency, and adherence to legal procedures in administrative decision-making. The PTUN ruled in favor of the Plaintiff, annulled the Regent's decision, and reinstated the Plaintiff to their previous position. This ruling reflects the principles of accountability and justice in public service, which must be upheld in governance.